Effect of NPK fertilization on the yield and yield stability of different maize genotypes - Krivián, Ágnes; Sárvári, Mihály (Acta Agraria Debreceniensis, 2012)
The yielding capacity and quality parameters of 11 maize hybrids were studied in 2011 on calcareous chernozem soil in a 25-year long-term fertilization experiment in the control (without fertilization), in the base treatment of N 40 kg ha-1, P2O5 25 kg ha-1, K2O 30 kg ha-1 and in five treatments which were the multiplied doses of the base treatment. The N fertilizer was applied in the autumn and in the spring, while P and K fertilizers were applied in the autumn.The sowing time was 17–18 April, the time of harvest was 8 October. The 30-year average of precipitation (April–Sept) was 345.1 mm, the amount of precipitation did not differ greatly from that, however, its distribution was very unfavourable.It was found that the largest yield increment (as compared to the control) was in the treatment N 40 kg ha-1, P2O5 25 kg ha-1, K2O 30 kg ha-1 in the long-term experiment. The largest yields were obtained for the hybrids P9494, PR37N01 and PR35F38 (13.64–13.71 t ha-1). Due to the dry period at the end of the summer – beginning of autumn, the grain moisture content at harvest was favourably low, 12–18% depending on the treatment and the growing season.The N fertilization significantly increased the protein content of the kernel, but the starch content of the kernel decreased (significantly in several cases) with increasing fertilizer doses and yields as compared with the control.The highest protein content was measured in hybrids GK Boglár and Szegedi 386. The oil content was above 4% for GK Boglár, but the two hybrids were not among the best yielding hybrids in spite of their good inner content. The starch content was around 75 % without fertilization, it decreased with fertilization.For the tested hybrids, the fertilizer dose N 120 kg ha-1, P2O5 75 kg ha-1, K2O 90 kg ha-1 can be recommended with respect to efficacy and environmental considerations.